Exploring Vocational High School EFL Teacher’s Understanding of Student-Centered Learning Assessment - Mardiant, Raniah; Kurniawan, Eri (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
Since the Kurikulum Merdeka was implemented to respond to the learning loss students experienced during the Covid-19 pandemic, student-centered learning assessment (SCLA) has become a significant part of current Indonesian senior high school educational initiatives. However, previous research found that teachers need more understanding of the concept of SCLA. Thus, this study explores vocational high school EFL teacher's understanding of SCLA in implementing problem-based learning in the Kurikulum Merdeka aligned with the theory from Jonassen (2000). This qualitative case study employed an interview as the main instrument to discover an understanding from one teacher. Based on the data analysis through thematic analysis, the findings revealed that the teacher had a fair understanding of the student-centered learning assessment's concepts, advantages, and obstacles. Nevertheless, the teacher still needed to learn more about SCLA. Although not all of the research findings were relevant to the previous study and the theory, the teacher reasonably implemented the student-centered learning assessment while improving the future teaching- learning process, particularly the assessment system. Moreover, there is an expectation for the school, principals, and other stakeholders to pay attention to providing teachers with training regarding student-centered learning assessment. In addition, teachers are expected to be willing to stay up-to-date with the change of curriculum, including the shift in the assessment form, teachers' role, and learning to understand the current curriculum and the learning methods.